Noise reduction inside a cavity coupled to a flexible plate with embedded 2-D acoustic black holes - Ji, Hongli; Wang, Xiaodong; Qiu, Jinhao; Cheng, Li; Wu, Yipeng; Zhang, Chao (Journal of sound and vibration, 2019)
Acoustic black hole (ABH) structures have been exploited to manipulate the flexural wave propagation with results showing a great potential for structural vibration damping enhancement and suppression of free-field acoustic noise radiation. In the present paper, ABHs are used to reduce the noise inside a cavity bounded by a flexible plate with multiple two-dimensional (2-D) ABH indentations. The interior sound field is generated by and fully coupled to the vibration of the flexible plate subject to a point force excitation. A refined numerical finite element model considering the plate-cavity coupling is established and validated by experiments. Both the simulation and experimental results show a significant noise reduction inside the cavity in a relatively wide frequency range through embedding the 2-D ABHs into the flexible plate. Analyses on the underlying mechanisms show a dual physical process of the ABH effects: the first being the direct consequence of the vibration reduction of the plate as a result of ABH-induced damping enhancement, whilst the second one being caused by a reduction in the coupling strength between the plate and the cavity. This ABH-specific decoupling phenomenon is characterized by the spatial coupling coefficients, which depend on the degree of morphological matching between structural modes and acoustic modes over the plate-cavity interface. The reported phenomenon of the impaired structural-acoustic coupling reveals a new ABH-specific feature which enriches the existing knowledge on ABH structures.